The Semantic Concept of Cohesion in Public Communication in the Croatian Language - Petrović, Bernardina; Gazdić-Alerić, Tamara (2012)
Cohesion is one of the most important factors of text creation. It is a semantic concept which occurs when the interpretation of one element in the text depends on some other element. Two mutually dependent elements form a cohesive connection, which means that one element presupposes the other in such a way that it cannot be decoded and understood without that other element with which it is semantically related. Due to the fact that cohesion is confirmed in the connections among the utterances within the text and it is represented through the use of lexical and semantic means, the use of cohesive means makes the communication easier for the recipient. Cohesion refers to the ways in which the components of the surface structure of the text are interconnected in the sequence. These surface components are mutually interdependent and are in accordance with grammatical forms and conventions. The paper presents the analysis of the semantic aspect of cohesive links in the assertive texts and media-transmitted public discourse in the Croatian language. Special attention will be paid to the description of functions of the four basic types of cohesion: reference, ellipsis, cohesion realized with connectors and lexical cohesion. These will be studied with regard to the outer and inner relationships which are established among those linking devices and which occur in the corpus collected. In the analysis of the examples of cohesive types, semantic as well as syntactical and pragmatic aspects of linking will be brought together. In other words, linking within a text will be studied in the entirety of the communication process.
ENG